Knowledge of future in context of retrospective analysis Critics and Replicas - M. V. Goncharenko (Омский научный вестник: Серия "Общество. История. Современность")
The article touches upon topical issues related to the problems of knowledge formation, including knowledge as foresight (knowledge about the future), which, according to the authors is impossible without the implementation of retrospective analysis. The author formulates the assumption that the process of the emergence of new knowledge is an integral part of the cultural state of society and is conditioned by the cultural memory and cultural achievements of particular epoch. In addition the research addresses the issues related to the inferential nature of knowledge: the contexts of opposing approaches are compared. The transformation of knowledge is an endless and non-interrupted process. The formation of knowledge about the future by a particular subject of knowledge seems doubtful and unsuccessful without the study and analysis of this process. In addition, the appeal to the problem of the transcendental pattern, forming knowledge, makes it possible to consider the inferential component of knowledge and its role in the creation of new sociocultural discourses